2015
DOI: 10.1530/eje-14-0756
|View full text |Cite
|
Sign up to set email alerts
|

Lack of utility of SDHB mutation testing in adrenergic metastatic phaeochromocytoma

Abstract: Objective: Testing for succinate dehydrogenase subunit B (SDHB) mutations is recommended in all patients with metastatic phaeochromocytomas and paragangliomas (PPGLs), but may not be required when metastatic disease is accompanied by adrenaline production. This retrospective cohort study aimed to establish the prevalence of SDHB mutations among patients with metastatic PPGLs, characterised by production of adrenaline compared with those without production of adrenaline, and to establish genotype-phenotype feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…This is also in agreement with other findings of high SSTR2 expression in PHEO/PGLs due to SDHB mutations 61 . These clinical findings support the possibility that utility of [ 177 Lu]Lu-DOTATATE reported here in the MPC-mCherry model may indeed translate to the clinic, and particularly to metastatic PHEO/PGLs due to SDHB mutations, which carry a high metastatic risk responsible for 40-50% of all cases of malignant disease 62 , 63 .…”
Section: Discussionsupporting
confidence: 78%
“…This is also in agreement with other findings of high SSTR2 expression in PHEO/PGLs due to SDHB mutations 61 . These clinical findings support the possibility that utility of [ 177 Lu]Lu-DOTATATE reported here in the MPC-mCherry model may indeed translate to the clinic, and particularly to metastatic PHEO/PGLs due to SDHB mutations, which carry a high metastatic risk responsible for 40-50% of all cases of malignant disease 62 , 63 .…”
Section: Discussionsupporting
confidence: 78%
“…PNMT catalyzes the final step of catecholamine biosynthesis from norepinephrine into epinephrine. Of particular interest, pseudohypoxic PPGLs are generally negative for PNMT, and have silent clinical and hormonal phenotypes, which could delay therapeutic intervention in such patients (93). Fukaya et al reported that lower DDC immunoreactivity was detected in poorly differentiated PPGLs, histologically representing confluent necrosis, diffuse growth, nuclear polymorphism, and tumor cell spindling (94).…”
Section: Catecholamine-synthesizing Enzymesmentioning
confidence: 99%
“…In a relatively large series of patients with metastatic PPGL, only a minority (11%) of patients had an adrenergic phenotype. Of note, none of these patients had a SDHB -related pheochromocytoma or paraganglioma [240]. The biochemical profile has also been linked to prognosis, as it was shown that patients with elevated plasma levels of dopamine and norepinephrine had a faster progression of their disease [239].…”
Section: Pheochromocytoma and Paragangliomamentioning
confidence: 99%